Syrian Heritage Archive Project. Projekt zur Erstellung digitaler Kulturgüterregister für Syrien. Das Archiv Hanspeter Hanisch der Projektphasen 2015 und 2016 - Bloch, Franziska; Gerth, Philipp (e-Forschungsberichte des DAI, 2017)
The Syrian Heritage Archive Project was launched in 2013 as a joint project between the DAI and the Museum of Islamic Art, Berlin. By creating a digital register of Syrian cultural heritage, it aims to preserve primary research data for the long term, and is gradually generating the basis for future work in the field of heritage conservation. Important archival records have been digitized and systematically integrated into the digital research environment of the DAI (iDAI.world). One of the most prominent data collections processed in 2015/2016 was the thorough documentation of the citadel of Damascus by the building researcher Hanspeter Hanisch.